Studies on Mass and Nutrients Balance During Enzymatic Hydrolysis of Cuttlefish Skin Waste - K. Elavarasan; M. D. Hanjabam; C. S. Tejpal; K. Sathish Kumar; A. A. Zynudheen (Fishery Technology, 2022)
Processed cuttlefish is one of the major seafood export commodities of India. Approximately 35% of raw material is converted into by-products during processing of cuttlefish. The cuttlefish skin waste (CSW) accounted to roughly 9% of the raw material and 28% of the by-products generated. In the present investigation, five different proteases namely alcalase, protease from Streptomyces griesus, protamex, papain and bromelain were screened for hydrolysis efficiency on CSW and found to produce soluble content of 80.65, 79.85, 73.47, 66.41 and 67.71%, respectively. Though the bacterial proteases were relatively more efficient in terms of soluble production based on the cost factor, papain was used for studying the mass and nutrients balance during the process of production than the plant proteases of cuttlefish skin protein hydrolysates. Papain enzyme was useful in converting the CSW in to two protein rich products namely water soluble protein hydrolysates and insoluble protein hydrolysates with 82.86 and 71.25% crude protein, respectively. The data presented would be useful for setting up industries for protein hydrolysates production from cuttlefish skin waste, which is abundantly available in India.